2016
DOI: 10.17795/intjsh-31198
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Attitude Toward Child Abuse Conducted in the Health Centers of Tabriz

Abstract: Background: Attitudes are very important in the formation of behaviors. Parents' attitudes toward children and behaviors with them are the main causes of child abuse. Identifying these attitudes and their related factors can be the primary basic action for prevention of child abuse. Objectives: This study was conducted to investigate the parents' attitudes toward child abuse in the health centers of Tabriz. Patients and Methods:In this cross-sectional study 384 parents with children 2 to 12 years old, filled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The research results confirm that people behave based on their attitudes, and in fact, many people's daily behaviors are influenced by their attitudes (Asadollahi et al, 2015). These studies have confirmed the relationship between attitude and behavior.…”
Section: Introductionsupporting
confidence: 76%
“…The research results confirm that people behave based on their attitudes, and in fact, many people's daily behaviors are influenced by their attitudes (Asadollahi et al, 2015). These studies have confirmed the relationship between attitude and behavior.…”
Section: Introductionsupporting
confidence: 76%
“…Parents’ attitude toward CM is a critical predictive factor of parental child abuse behavior (Stith et al, 2009). Several studies have shown that parents with more positive beliefs or values toward CM tend to show more child abusive behaviors than parents with a negative attitude (Asadollahi et al, 2016; Ateah & Durrant, 2005; Bower-Russa, 2005; Chavis et al, 2013; Stith et al, 2009; Vittrup et al, 2006). For this reason, a number of studies on CM prevention used instruments to measure parents’ attitude toward CM as an outcome measure to establish whether the programs being evaluated are effective (Chen & Chan, 2016; Gershoff et al, 2017; Holden et al, 2014; Voisine & Baker, 2012).…”
mentioning
confidence: 99%
“…Also, many instances of child abuse stem from parents', especially mothers', insufficient knowledge about how to properly interact with their children and the consequences of this phenomenon. It is worth mentioning that in some cases, parents hold incorrect beliefs and attitudes that legitimize abusive behaviors (Asadollahi et al, 2016). Therefore, since a significant portion of abuse against children is perpetrated by their mothers, to control the level of violence against children, parents must be directly educated about the precursors and consequences of child abuse to prevent this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Many cases of child abuse result from parents' ignorance about how to interact properly with their children and the consequences of this phenomenon. It should be noted that in some cases, parents have incorrect beliefs and attitudes that justify abusive behaviors (Asadollahi et al, 2016).…”
mentioning
confidence: 99%